Correlation Structure of Library Circulation Data:A Case Study:Part 2-Theoritical Aspect - Burrell, Quentin L. (Journal of Information and Knowledge, 2014)
The theory of mixtures of point processes is used to provide models for library circulation data. The extent to which such models are able to mimic the observed correlation structure is investigated making use of the so-called Poisson regression ratio. Particular reference is made to the University of Saskatchewan database analyzed in Part 1 of this study.